Water spinach (Ipomoea reptans) nutrient leaching and water loss in three irrigation systems - Jaafar, Akmal Hafiz (2015)
Rb 900 tube also known as root trainer is a new way to replacing polybag that use with BX-1 media. Rb 900 tube and BX-1 media is still new in Malaysia, there is no scientific test has been done on these Rb 900 and BX-1 systems. The advantages if compare with polybag are, root growth is more vigorous and rapidly. The plant survival is better than polybag. Root trainer also reduce the space requirements in the nursery and transport costs to the field but most interesting is plants grown in root trainer systems are often ready for planting out when they are substantially smaller than those from conventional polybag. The objective of this experiment was to make a comparison between each of the irrigation which is the most suitable in term of nutrient leaching. This experiment was conducted at Field No. 15, Universiti Putra Malaysia under the rain shelter for 5 weeks in July 2014. The experimental layout was the Randomised Complete Block Design (RCBD). The treatments were the three irrigation system: overhead sprinkler (T1), drip irrigation (T2) and capillary wick system (T3) with 3 replications per treatment. Consequently, the experimental units or plots were 9. Each plot was planted with 10 water spinach plants, so the total seedling planting for this experiment was 90 plants. Result from the study showed that capillary wick system produced least leachate in volume and nutrients loss. The mean cumulative for volume of was 292.60 ml and for the nutrients N, P, K, Ca, Mg - 201.80 N mg L-1, 152.06 P mg L-1, 264.00 K mg L-1, 17.698 Ca mg L-1, 24.99 Mg mg L-1. Thus, capillary wick system was the most effective irrigation suggested to be used with BX-1 and Rb 900.